The first conference of the SK BiH in 1988 and the staff differentiation in the SR Bosnia and Herzegovina - Sarač Rujanac, Dženita (Historical Thought, 2024)
Based on the press, partially available and unregistered archival material, and published sources, the paper points to the efforts of the League of Communists of Bosnia and Herzegovina to find a way out of the complex economic, political, and social crisis during the second half of the 1980s. At the same time, the democratization of overall social relations and political practice was emphasized as a priority, and a significant role was to be played by the so-called democratization of personnel policy. Personnel renewal and differentiation within the League of Communists gained importance due to the revelation of a series of cases and affairs. Those affairs highlighted the disconnection between the leadership and the base and were interpreted as the result of years of abuse of position and authority, disrespect for the Constitution and evasion of the law. Particular attention in the paper is devoted to the First Conference of the League of Communists of Bosnia and Herzegovina, held in April 1988, where these issues were discussed.